Financial Funding for Small and Medium-sized Enterprises (SMEs) - Ni Nyoman Sawitri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this paper is to provide a comprehensive understanding of SME funding issues and promote more inclusive and sustainable funding approaches for SMEs. The method used in this paper is qualitative by looking for papers derived from existing journal literature within ten years, looking for findings or results related to variables in this paper. Discuss results and findings from the literature found. The results of this paper after being presented in the form of a conclusion that makes contributions related to the field of finance. SMEs have an important role to play in African economies, but they often struggle to access formal financial services. Informal finance is becoming the preferred choice in some situations. Recommendations include building a regulatory framework, increasing linkages between the formal and informal financial sectors, and leveraging financial technology (FinTech) for financial access. Financial inclusion and risk management of SMEs are also important. This conclusion highlights the role of SMEs and the financial challenges that must be overcome to support economic growth.